2021
DOI: 10.7554/elife.67828
|View full text |Cite
|
Sign up to set email alerts
|

Targeting an anchored phosphatase-deacetylase unit restores renal ciliary homeostasis

Abstract: Pathophysiological defects in water homeostasis can lead to renal failure. Likewise, common genetic disorders associated with abnormal cytoskeletal dynamics in the kidney collecting ducts and perturbed calcium and cAMP signaling in the ciliary compartment contribute to chronic kidney failure. We show that collecting ducts in mice lacking the A-Kinase anchoring protein AKAP220 exhibit enhanced development of primary cilia. Mechanistic studies reveal that AKAP220-associated protein phosphatase 1 (PP1) mediates t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“… 18 , 19 AKAPs also integrate subcellular signals from other kinases and effector enzymes at sites proximal to their substrates. 20 23 Signaling through AKAPs limits the range and duration of information relay within cells. 24 26 In this report, we show that DNAJ-PKAc preferentially interacts with a particular spectrum of binding partners.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 AKAPs also integrate subcellular signals from other kinases and effector enzymes at sites proximal to their substrates. 20 23 Signaling through AKAPs limits the range and duration of information relay within cells. 24 26 In this report, we show that DNAJ-PKAc preferentially interacts with a particular spectrum of binding partners.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the AKAP11-involved cAMP/PKA signaling inhibits gene transcription by phosphorylating HDACs, such as HDAC5, and preventing their export from the nucleus 25 . In addition, AKAP11-PP1 complex can affect HDAC6 stability 85 . Moreover, AKAP11-PKA-regulated GSK3B, one of the molecular targets of lithium, which is the most common medication to prevent recurrences of both manic and depressive episodes in BD patients [18][19][20][21] , has been suggested to be involved in the regulation of HDAC6 activity through phosphorylation events 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Compartmentalization though association with A-kinase anchoring proteins (AKAPs) is a mechanism that imparts specificity to PKA signaling 18,19 . AKAPs also integrate subcellular signals from other kinases and effector enzymes at sites proximal to their substrates [20][21][22][23] . Signaling through AKAPs limits the range and duration of information relay within cells [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%